Rising above institutional constraints: the quest of german accreditation agencies for autonomy and professional legitimacy - Serrano-Velarde, Kathia (Minerva, 2014)
European quality assurance has a complicated history that must be viewed as taking place on two levels: first, in a national effort to deregulate the public sector and to make universities accountable for their teaching performance; and second, a supranational endeavor to accomplish European integration in the field of higher education. Similarly, the web of institutional constraints and opportunity structures in which accreditation agencies are embedded spans two policy levels, the national and the European. In this paper, we examine how German accreditation agencies achieve some level of autonomy in a highly entrenched institutional environment. The paper is based on a qualitative study comprising archival data and over 70 semi-structured interviews. Drawing on the insights of neo-institutional theory, we argue that quality assurance agencies seek political leverage at the European level in order to strengthen their standing in the higher education systems of their own countries.